Mujeres con VIH-SIDA en el Hospital Nacional Cayetano Heredia en Lima, Perú. - SOLARI ZERPA, Lely (2013)
Objective: The aim of this study is to describe the epidemiological and clinical characteristics of the women infected with the Human Inmunodefficiency Virus (HIV) who were seen at the Hospital Nacional Cayetano Heredia from January 1989 to December 1996. Material and Methods: We did a retrospective chart review of their demographic and medical registers. We used the Centres for Disease Control (CDC) classification for the HIV infection. (Stages I-IV). Results: We included 236 women, from 17 to 60 years old, with a mean age of 30.4 years. The number of diagnosed cases per year of infected women increased from 5 in 1989 to 63 in 1996. The probable means of acquisition of infection was heterosexual intercourse in 212 patients (90.2%). Only had one sexual partner in her life 113 (47.8%) of the patients seen. There were 4 (1.6%) sexual workers and there were no intravenous drug users. A percentage of 23.4% have had other Sexually Transmitted Diseases (STD), and these were more prevalent in women who had risky sexual practices (p=0.005). Out of the 236, 69 women had diagnosis of Acquired Inmunodefficiency Syndrome (AIDS) The most frequent AIDS-defining condition was the Wasting Syndrome in 23 women (33.3%). There were 19 deaths within the study period. The mean survival time after the AIDS diagnosis was 10.6 months and the most frequent death cause was Tuberculosis and Pneumocystis carinii Pneumonia. Conclusion: The fact of having a predominantly heterosexual transmission and that there is a high percentage of monogamous women and women with few sexual partners make us suppose that it is probably their partners risk sexual behavior what exposes women to HIV infection. We must underline the importance of an adequate information to women who start their sexual life and of the risks these bring, and the diffusion of the use of condoms to prevent this infection.